Perubahan kualitas hidup akibat pandemi COVID-19: Analisis klaster provinsi di Indonesia - Ruth Meilianna; Juan Palem Sinaga; Riskie Ulvat Dinnita (Research Centre for Population, National Research and Innovation Agency (BRIN), 2021)
Good quality of life is an essential aspect of human capital development. The impact of COVID-19 pandemic not only influenced critical economic sector, such as unemployment problem, but also affected fulfilment of basic needs, such as health, education, assets ownership that are indicators of quality of life in the community. The effect of the COVID-19 pandemic on the quality of life in provinces in Indonesia may vary, given the different levels of spread of COVID-19 in each province. This study aims to create clustering based on the level of quality of life of provinces in Indonesia and review whether there were cluster changes among the cluster members due to the COVID-19 pandemic and whether the position of the cluster changed from the centroid position after the COVID-19 pandemic. The data used in this study are life expectancy, school expectancy, economic growth rate per capita, and percentage of homeownership in 2018-2020. The method used is K-Means using the Rapid Mining Studio tool. The results showed changes in the provincial clusters from the transition period to the period after the COVID-19 pandemic.health; education; economy; cluster; quality of life; COVID-19 pandemic